Adsorption characteristics of Cr(VI) on microalgae immobilized by different carriers. Issue 7 (7th June 2022) - Wang, Junjun; Liang, Qiu; Cui, Linlin; Wu, Xueling; Li, Jiaokun; Zeng, Weimin; Shen, Li
Abstract: To solve the problem of harvesting microalgae during heavy metal adsorption, six different carriers were selected in this study to compare the adsorption behavior of microalgae after immobilization. The results of the scanning electron microscope (SEM) and adsorption showed chitosan as a carrier showed the best immobilization effect and adsorption advantages after immobilizing microalgae. The optimal immobilized carrier-chitosan was obtained under the following conditions of chitosan: acetic acid (2:40), microalgae concentration (10 8 cells mL −1 ), and immobilization time (18 h). The optimal adsorption conditions were as follows: temperature: 30 °C, pH: 7.0, adsorption dose: 1.5 g L −1, initial ion concentration: 40 mg L −1 . The adsorption capacity of metal ions can reach 37.1 mg g −1 Cr(VI), 25.98 mg g −1 Cu(II), 25.06 mg g −1 Pb(II), and 24.62 mg g −1 Cd(II), respectively. The desorption efficiency in 0.5 mol L −1 NaOH desorption solution reached 90.01%. After five adsorption-desorption cycles, excluding chitosan (∼70%), the adsorption efficiency of other adsorbents decreased with an increase in the recycling times. Chitosan was a suitable carrier for the immobilization of Synechocystis sp. PCC6803. Fourier transform infrared spectroscopy and Raman spectra analysis showed that groups belonging to the microalgae were detected after the microalgae in different carriers, indicating that the microalgae were immobilized with the carriers. At the same time, the energy spectrum changed before and after adsorption indicated the specific functional groups of microalgae played an important role in the adsorption process. The kinetic and isothermal model data showed that the adsorption process was mainly chemical adsorption and homogeneous monolayer adsorption. Moreover, X-ray diffraction showed the interlayer peak strength decreased significantly, indicating that the interlayer structure was stretched after Cr(VI) ion exchange. X-ray photoelectron spectroscopy analysis showed that the Cr adsorption process involves the reduction of Cr(VI) to Cr(III). Novelty statement: The application of immobilization technology in various aspects of microalgae has attracted the attention of researchers. At present, the research report mainly focuses on the parameter optimization of microalgae immobilized by the carrier, but there are few reports on the comparison of different carriers for microalgae immobilization and the study on the adsorption mechanism of heavy metals by the optimal carrier for microalgae immobilization. In this study, six different carriers were selected to compare the effects of microalgae immobilization, and the optimal carrier was obtained. To further explore the optimal synthesis parameters of the suitable carrier, the optimal adsorption parameters for heavy metals, desorption efficiency, and recycling effect, explore the adsorption mechanism, and provide a feasible basis and theoretical guidance for the extensive application of microalgae immobilization technology in the industry.